The iron curtain: what pro-choice and pro-life organizations in Kansas learn from each other through communication - Weston, George H. (Kansas State University, 2012)
The purpose of this research started with a Cold War perspective of looking at the Pro-Choice and Pro-Life movement in the state of Kansas. They are in opposition of one another, so how do they communicate and see one another? Interviews were done in four cities in Kansas and with one organization located in Kansas City, Missouri that is responsible for their national organization’s mission in Kansas. Eighteen individuals were interviewed, which was split evenly with nine Pro-Choice and nine Pro-Life advocates in leadership or communication positions. Race, sex, religion, and age are all considered in the research. Most of the Pro-Choice organizations were found to be focused on multiple issues besides abortion, while all but one of the Pro-Life organizations were focused on the issue of abortion almost exclusively. There was a regional disconnect that showed a major difference of the thinking between the Kansas City metro area based organizations and the Wichita area based organizations, as the Wichita area advocates spoke more in detail about the events of the Summer of Mercy in 1991 and the death of Dr. Tiller in 2009. The research found that the Cold War analogy of the two sides works to only an extent, as the messages sent out are not directly sent to one another, even though both sides read what their opposition is saying. There might be subconscious messaging going on with some knowing the opposition is reading what they have to say. The learning factor for opposition organizations is that they are learning news tactics and how they should counter the actions and messages of the other side. Almost all direct communication between the two sides has been cutoff, thus that is where the Cold War analogy falls short as a comparison because both sides feel there is no agreeable middle ground or purpose for negotiations.
Keywords: Non-Profit; Communication; Social Research (0344)